2012
DOI: 10.1016/j.drugalcdep.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent exposure to nicotine results in reinforcement enhancement but does not affect adult responding in rats

Abstract: Background Adolescence is a period of development associated with a peak in an organism’s responsiveness to reward. Epidemiological data indicate that the initiation of smoking is high during adolescence and that earlier age of onset is associated with increased incidence of dependence as adults. In rats, nicotine is known to have primary reinforcing and reinforcement enhancing effects. Although the primary reinforcing effects of nicotine have been demonstrated in adolescent rats (self-administration), less is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Bracken et al (2011) recently confirmed that adolescent nicotine induces adult nicotine sensitization in the rat. In addition to lasting changes in sensitization, adolescent nicotine leads to enhanced self-administration of nicotine in adult mice (Adriani et al, 2006) and rats ; this, however, was not confirmed by Weaver et al, (2012) in rats.…”
Section: Addiction-related Behavioral Changesmentioning
confidence: 86%
“…Bracken et al (2011) recently confirmed that adolescent nicotine induces adult nicotine sensitization in the rat. In addition to lasting changes in sensitization, adolescent nicotine leads to enhanced self-administration of nicotine in adult mice (Adriani et al, 2006) and rats ; this, however, was not confirmed by Weaver et al, (2012) in rats.…”
Section: Addiction-related Behavioral Changesmentioning
confidence: 86%
“…We used a procedure that is well established in our laboratory, in which rats respond for a moderately reinforcing VS and receive non-contingent nicotine (Caggiula et al, 2009;Donny et al, 2003;Rupprecht et al, 2015;Weaver et al, 2012). We showed that MAO inhibition decreased the threshold nicotine dose required for reinforcement enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The nicotine dose was increased across sessions: 0.03 mg/kg (10 sessions), 0.1 mg/kg (5 sessions), and 0.3 mg/kg (4 sessions). The first two doses (0.03, 0.1 mg/kg) are relatively low s.c. doses of nicotine not expected to enhance the value of the VS on their own (unpublished observations), and the highest nicotine dose (0.3 mg/kg) is a dose in the range expected to enhance the value of the VS (Buffalari et al, 2014;Weaver et al, 2012;Wing and Shoaib, 2010). For this experiment, sessions were conducted 5 days per week.…”
Section: Experiments 4: Impact Of Mao Inhibition On Threshold For Reinmentioning
confidence: 99%
“…Generally speaking, decreases in drug reward sensitivity are often associated with compensatory increases in drug self-administration under relatively low levels of response effort (see Koob & LeMoal, 2006). Indeed, age-specific enhancement of self-administration of nicotine (Adriani et al, 2003, 2006) and cocaine (McQuown et al, 2007; Dao et al, 2011) has sometimes (albeit not always – see Weaver et al, 2012; Levin et al, 2011) been reported after adolescent exposure to nicotine, with these effects generally restricted to exposures during early-mid adolescence, and not late adolescence or adulthood. This enhanced self-administration does not extend to all types of rewards given that similar effects were not evident when animals were given the opportunity to self-administer sucrose pellets (McQuown et al, 2007).…”
Section: Nicotinementioning
confidence: 99%